2013
DOI: 10.1007/s12032-013-0800-8
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin lymphoma transformation of chronic lymphocytic leukemia: cases report and discussion

Abstract: B-cell chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is the most common form of leukemia affecting adults in Europe and North America. Large B-cell lymphoma known as Richter’s syndrome (RS) may develop approximately in 3–15 % patients. Furthermore, other hematological malignancies may also occur as RS variants, among them—Hodgkin lymphoma (HL). CLL/SLL transformation into HL is observed in about 0.5 % of patients, and till now, fewer than 100 cases have been reported in the medical literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…Our analysis confirms that HvRS can develop anytime since CLL/SLL diagnosis, being however a late event in the majority of patients. In our study, the median time of 3.2 years to HvRS from CLL/SLL diagnosis was shorter than the time reported by others (4.6‐7.5 years) . It is difficult to explain but it might be simply a consequence of relatively late diagnosis of neoplastic diseases in Poland, especially if asymptomatic as in the case of CLL .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our analysis confirms that HvRS can develop anytime since CLL/SLL diagnosis, being however a late event in the majority of patients. In our study, the median time of 3.2 years to HvRS from CLL/SLL diagnosis was shorter than the time reported by others (4.6‐7.5 years) . It is difficult to explain but it might be simply a consequence of relatively late diagnosis of neoplastic diseases in Poland, especially if asymptomatic as in the case of CLL .…”
Section: Discussioncontrasting
confidence: 70%
“…Our study included 22 patients with HvRS diagnosed between 2002 and 2016 at 10 PLRG centers. Twelve patients have been reported earlier . The median age at CLL/SLL diagnosis was 59 years (range: 39‐77), only three (14%) patients were older than 70 years.…”
Section: Resultsmentioning
confidence: 99%
“…About 2–8 % of patients with CLL/SLL develop diffuse large B‐cell lymphoma (RT‐DLBCL), the most common type of transformation, followed by classical Hodgkin lymphoma (RT‐CHL) in <1 % patients . However, the definition is still controversial: some authors restricted the term RS only to those developing DLBCL, so‐called “true or classical RT” . RT is an aggressive disease, with a median survival of less than one year .…”
mentioning
confidence: 99%
“…[20,26,30,31] While different pathogenetic mechanisms are discussed in both types of transformation, only type 2 is considered as true Hodgkin transformation irrespective of clonal relationship with the underlying CLL cells. [6,20,[29][30][31][32] In our patient, morphological and immunohistochemical findings at autopsy showed classical HL, namely type 2 transformation. Approximately half of CLL cases carry a mutation in the variable region of the IGHV gene.…”
Section: Discussionmentioning
confidence: 92%
“…[20,25] Generally, clinical outcomes are worse than in de novo HL. [20,25,32] A retrospective analysis demonstrated that patients previously treated for CLL with fludarabine displayed a more aggressive course of HL and a shorter mean survival of 0.7 years compared to 2.1 years in the non-fludarabine group. [20] …”
Section: Discussionmentioning
confidence: 99%